2022
DOI: 10.1016/j.msard.2022.103486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 antibody response after two doses of mRNA and inactivated vaccines in multiple sclerosis patients treated with disease-modifying therapies

Abstract: Background: Disease-modifying therapy could weaken the immune system and decrease the immune response to vaccines. It is essential to know which vaccine is more protective against SARS-CoV-2 in the multiple sclerosis population. Objective: To assess immune response after messenger RNA BNT162b2 (Pfizer/BioNTech) and inactivated Sinovac vaccines in people with multiple sclerosis (pwMS) treated with a disease-modifying therapy (DMT) compared to healthy controls. Methods: This single-centre c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 16 publications
3
38
1
Order By: Relevance
“…High-certainty evidence confirms significantly lower odds of post-vaccination seroconversion in pwMS on S1PRM compared with UX people (OR [95%CI]: 0.04 [0.03, 0.06], P<0.00001) (Supplementary Figure 5). All included studies 16,17,19-22,25-31 found significantly lower concentrations of antibodies following vaccination in these pwMS compared to UX people. Studies with heterogenous effect measures (moderate-certainty evidence) indicate that with the current vaccination strategy, pwMS on S1PRM are 25 times (95%CI: 16.66, 33.33) less likely to show anti-S1, and 8.33 times (95%CI: 3.70, 20) less likely to show anti-S seroconversion following COVID-19 vaccination (Chi 2 =7.24, P<0.01).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…High-certainty evidence confirms significantly lower odds of post-vaccination seroconversion in pwMS on S1PRM compared with UX people (OR [95%CI]: 0.04 [0.03, 0.06], P<0.00001) (Supplementary Figure 5). All included studies 16,17,19-22,25-31 found significantly lower concentrations of antibodies following vaccination in these pwMS compared to UX people. Studies with heterogenous effect measures (moderate-certainty evidence) indicate that with the current vaccination strategy, pwMS on S1PRM are 25 times (95%CI: 16.66, 33.33) less likely to show anti-S1, and 8.33 times (95%CI: 3.70, 20) less likely to show anti-S seroconversion following COVID-19 vaccination (Chi 2 =7.24, P<0.01).…”
Section: Resultsmentioning
confidence: 93%
“…Moderate-certainty evidence did not suggest decreased odds of post-vaccination seroconversion in the pwMS on GA compared to the UX people (OR [95%CI]: 0.87 [0.31, 2.42], P=0.79) (Supplementary Figure 2). Post-vaccination seronegative pwMS on GA were only present in two studies 21,22 – all being among the ones receiving inactivated vaccination. Quantitative analysis in suggested no difference in post-vaccination antibody concentrations between GA-treated pwMS and the UX people in any study.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations